Burden of Multidrug-Resistant Organisms in Oman: A Six-Year Single-Study Calling for Urgent Actions - Mohammed Abdullah Al Shuhoumi; Suleiman Al Ghafri; Fareed J. Hameed; Asma Al Hinai; Abir Al Ghafri; Sathiya R. Mony; Bader Al Sawafi; Gopinath Govindaraj; Asma Al Yaqoobi; Badryia Al Alawi; Vinod Arora; Amani H. Al Waili; et al. (Microbiology Research, 2025)
Background: Healthcare facilities worldwide are struggling to combat the increasing prevalence of multidrug-resistant organisms (MDROs). MDROs pose a serious threat to patient safety, resulting in longer hospital stays, higher healthcare expenses, and increased mortality rates. Oman aims to enhance patient safety by implementing data-driven strategies for infection control protocols. MDRO studies are limited, with only one-year data available from a tertiary hospital. No comprehensive six-year study has been released from Oman, leaving a gap in understanding the true burden of MDROs in the country. Methods: A 6-year retrospective cross-sectional analysis of MDRO files at Ibri Regional Hospital was conducted from 1 January 2017 to 31 December 2022 on clinical samples (urine, pus, eye, ear, tissue, fluid, wound, CSF, blood, ET, and sputum culture). Non-clinical and duplicate samples were excluded. Two prevalence rates were calculated: isolates and patients per 1000 admissions. Isolates were identified using the API system, VITEK-2, and MALDI-TOF MS. CLSI guidelines that are updated annually were used for antibiotic susceptibility testing. Statistical analysis was performed using SPSS to identify significant associations between pre-established variables. Ethical approval was obtained from the Centre for Studies and Research (MOH/CSR/26193). Results: MDRO prevalence in our cohort (1846 cases) was illustrated per isolate and per patient (1000 admission) and showed a growing trend; 25.60:18.70/1000 (2017), 24.40:22.40/1000 (2018), 26.80:19.40/1000 (2019), 31.20:21.70/1000 (2020), 32.50:19.00/1000 (2021), and 31.70:20.40/1000 (2022). Urinary infections were predominant, followed by surgical, respiratory, blood, and neurological infections. Respiratory infections increased during the COVID-19 era. ESBL remained the primary burden, followed by Acinetobacter MDR, MRSA, CRE, pseudomonas MDR, and VRE. VRE showed a spike in 2021 but returned to baseline in 2022. Conclusions: The study reveals a growing trend of MDROs in Oman, with species prevalence similar to that of adjacent countries. Urgent actions needed include national antibiotic policies, a local antibiogram database, public awareness campaigns on antibiotic resistance, and predicting bed occupancy for expansion/construction programs.